1998
DOI: 10.1002/(sici)1521-3765(19981204)4:12<2493::aid-chem2493>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic/Organic Mesostructures with Complex Architectures: Precipitation of Calcium Phosphate in the Presence of Double-Hydrophilic Block Copolymers

Abstract: Double-hydrophilic block copolymers consisting of a long poly(ethylene oxide) block and a short poly(methacrylic acid) block, modified by partial alkylation with dodecylamine (PEO-b-PMAA-C 12 ) were employed as dispersed templates for the controlled precipitation of calcium phosphate from aqueous solution at different pH values. Two new and nontrivial superstructures of an organized inorganic/organic hybrid material were characterized by ultracentrifugation, small-and wide-angle X-ray analysis, and electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
2
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 228 publications
(176 citation statements)
references
References 8 publications
9
159
2
6
Order By: Relevance
“…One aspect that should be borne in mind in all the above experiments is that in spite of the remarkable structures that TW can form, bulk crystallization does still take place and the coexistence of the stabilized amorphous neuron-like structure along with the crystallized phase complicates the interpretation of results. The close similarity between the neuron-like structures obtained with this simple surfactant and those discovered by Antonietti et al 20 using DHBCs clearly prove that such structures are not specic of the complex copolymer. To further reinforce this aspect, additional experiments were performed using a different surfactant.…”
Section: Calcium Phosphate Precipitation In the Presence Of Surfactantssupporting
confidence: 78%
See 4 more Smart Citations
“…One aspect that should be borne in mind in all the above experiments is that in spite of the remarkable structures that TW can form, bulk crystallization does still take place and the coexistence of the stabilized amorphous neuron-like structure along with the crystallized phase complicates the interpretation of results. The close similarity between the neuron-like structures obtained with this simple surfactant and those discovered by Antonietti et al 20 using DHBCs clearly prove that such structures are not specic of the complex copolymer. To further reinforce this aspect, additional experiments were performed using a different surfactant.…”
Section: Calcium Phosphate Precipitation In the Presence Of Surfactantssupporting
confidence: 78%
“…[16][17][18][19] Particularly in the calcium phosphate system, Antonietti et al reported back in 1998 the stabilization of delicate neuron-like calcium phosphate structures with the help of a DHBC consisting of a long poly(ethylene oxide) block and a short poly(methacrylic acid) block partially alkylated with dodecylamine (PEO-block-PMMA-C12). 20 These structures were again replicated by Tjandra et al in 2005 using a similar design of the DHBC (PEO-block-PMMA) but with a longer PMMA chain. 21 The need for the complex DHBC seemed mandatory for the formation of such structures, and the mechanism of formation was believed to occur via formation of micelle aggregates of the copolymer.…”
Section: 10mentioning
confidence: 75%
See 3 more Smart Citations